Use of antenatal services and delivery care among women in rural western Kenya: a community based survey - Rosen Daniel H; Blokland Ilse E; Ayisi John G; Odhiambo Frank; Bles Hanneke M; van Eijk Anna M; Adazu Kubaje; Slutsker Laurence; Lindblade Kim A (BMC, 2006)
Abstract Background Improving maternal health is one of the UN Millennium Development Goals. We assessed provision and use of antenatal services and delivery care among women in rural Kenya to determine whether women were receiving appropriate care. Methods Population-based cross-sectional survey among women who had recently delivered. Results Of 635 participants, 90% visited the antenatal clinic (ANC) at least once during their last pregnancy (median number of visits 4). Most women (64%) first visited the ANC in the third trimester; a perceived lack of quality in the ANC was associated with a late first ANC visit (Odds ratio [OR] 1.5, 95% confidence interval [CI] 1.0-2.4). Women who did not visit an ANC were more likely to have < 8 years of education (adjusted OR [AOR] 3.0, 95% CI 1.5-6.0), and a low socio-economic status (SES) (AOR 2.8, 95% CI 1.5-5.3). The ANC provision of abdominal palpation, tetanus vaccination and weight measurement were high (>90%), but provision of other services was low, e.g. malaria prevention (21%), iron (53%) and folate (44%) supplementation, syphilis testing (19.4%) and health talks (14.4%). Eighty percent of women delivered outside a health facility; among these, traditional birth attendants assisted 42%, laypersons assisted 36%, while 22% received no assistance. Factors significantly associated with giving birth outside a health facility included: age ≥ 30 years, parity ≥ 5, low SES, < 8 years of education, and > 1 hour walking distance from the health facility. Women who delivered unassisted were more likely to be of parity ≥ 5 (AOR 5.7, 95% CI 2.8-11.6). Conclusion In this rural area, usage of the ANC was high, but this opportunity to deliver important health services was not fully utilized. Use of professional delivery services was low, and almost 1 out of 5 women delivered unassisted. There is an urgent need to improve this dangerous situation.